The Influence of Social Media Marketing on Purchase Decision through Brand Image and Brand Trust on Larutan Penyegar Cap Badak - Krisnandiva, Radya Ayu; Nurhayati, Popong; Yuliati, Lilik Noor (ASEAN Marketing Journal, 2024)
Manuscript type: Research article Research Aims: To investigate the influence of social media marketing on purchase decisions through brand image and trust focusing on Larutan Penyegar Cap Badak. Design/methodology/approach: Data was collected from December 2023 to January 2024 using Google Forms in Indonesia. The respondents of this study are Instagram users aged over 17 years who have purchased Larutan Penyegar Cap Badak. This study used SEM-PLS analysis with a total of 205 respondents. Research Findings: The result shows that social media marketing has a positive and significant effect on brand image, brand trust, and purchase decisions. Brand image has a positive and significant impact on brand trust. Brand trust has a positive and significant effect on purchase decisions. Also, social media marketing has a positive and significant impact on purchase decisions through the mediating variable of brand trust. Meanwhile, brand image does not have a significant impact on purchase decisions. Social media marketing does not have a significant effect on purchase decisions through the mediating variable brand image. Theoretical Contribution/Originality: Provide insight regarding the value that drives purchase intention on Larutan Penyegar Cap Badak using social media marketing. Practitioner/Policy Implication: Provide insight to improve Larutan Penyegar Cap Badak’s social media marketing and contribute to consumer behavior understanding of health products. Research limitation/Implication: Only limited to the usage of one social media platform which is Instagram. Future studies could investigate other social media platforms to find preponderant findings.